Challenges and opportunities of mobile payments innovations - Proença, João Miguel Vieira Campos de Frias (2018)
Innovation in financial services is a major trend on the sector and the payments industry is no exception to that. New ways of paying, as mobile payments, are emerging and changing the payments market. Non-financial institutions are entering the market through the provision of mobile payments, threatening the dominant position banks hold in the industry. This thesis aim is to analyze mobile payments as a service innovation, primarily through the spectrum of banks as old incumbents in this market. To understand the traits and main characteristics of these products, as well as how innovation in mobile payments is changing or even creating a new market. The results of the study suggest that we are facing a radical innovation, according to the Gallouj and Weinstein (1997) modes and models of innovation, as there is a completely new system behind mobile payments services. This innovation is assuming different forms and is still hard to infer if mobile payments are creating a new market, as these kind of services are still majorly seen by experts in the area, who were interviewed for this study, as a complement to other ways of paying, regardless of being a complete new system with different competences needed for operating. With regard to the new and different providers of these services operating in the market, it was found that they can be segmented into three clusters with different characteristics: Banks, which are the traditional incumbents of this market; Mobile Network Operators & Manufacturers, which are extremely focused on technology and data; Others, which include companies from other sectors, fintechs or other startups, characterized by being very innovative and flexible. These new services come with new market dynamics involving companies that traditionally were not associated with the provision of financial services, and threatening the relevance banks used to have in the payments industry.